2019
DOI: 10.15244/pjoes/94388
|View full text |Cite
|
Sign up to set email alerts
|

Validating Models for Calculating the Efficiency of Earth-to-Air Heat Exchangers Based on Laboratory Data for Fall and Winter 2016 in Northeastern Poland

Abstract: Contemporary energy-saving mechanical ventilation systems combined with Earth-Air Heat Exchangers (EAHE) can reach high energetic and economic efficiency. The necessary condition for optimisation of ventilation system functioning is the adequate design of EAHE. This requires knowledge of soil temperature distribution in the location of EAHE. It constitutes a complex problem because of the influence of different factors. The correct estimation of soil temperature for a given location can be difficult in the des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The issue of the efficiency of heat extraction from the ground remains an open question. Testing on the ground-coupled pipe heat exchanger located at the Research Laboratory, conducted under the actual operational conditions, demonstrated that continuous operation under summer and transitional conditions is ineffective [79]. On the other hand, under winter conditions, the device enables efficient heat extraction from the ground [80].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The issue of the efficiency of heat extraction from the ground remains an open question. Testing on the ground-coupled pipe heat exchanger located at the Research Laboratory, conducted under the actual operational conditions, demonstrated that continuous operation under summer and transitional conditions is ineffective [79]. On the other hand, under winter conditions, the device enables efficient heat extraction from the ground [80].…”
Section: Resultsmentioning
confidence: 99%
“…The result analysis demonstrated that the average coefficient of performance (COP) value was 3.36 and ranged from 2.24 to 4.46, while the COP catalog value declared by the manufacturer was 4.57. The emission analysis (Table 5) was conducted based on the indices of pollutant emission from fuel combustion in boilers with a nominal thermal power of up to 5 MW, according to the National Centre for Emissions Management (KOBiZE) [79]. The analysis results are presented in Table 4.…”
Section: Resultsmentioning
confidence: 99%
“…Skotnicka-Siepsiak et al [53][54][55] discussed results of experiments and simulations of EAHE for a residential building in Olsztyn (northern Poland). Analyses performed on the basis of measurements taken in October, November and December of 2016 were presented in [54].…”
Section: Introductionmentioning
confidence: 99%
“…Skotnicka-Siepsiak et al [53][54][55] discussed results of experiments and simulations of EAHE for a residential building in Olsztyn (northern Poland). Analyses performed on the basis of measurements taken in October, November and December of 2016 were presented in [54]. Authors focused on comparison of measured energy gains with values calculated from two different theoretical models of soil temperature distribution.…”
Section: Introductionmentioning
confidence: 99%
“…In Poland, GAHEs are increasingly often used to preheat air, both in small ventilation systems in single-family homes and in large installations where the diameter of ground tubes exceeds 900 mm [3]. The performance of a GAHE in the winter of 2016 was analyzed by [4]. The experimentally measured values were compared with theoretical computational models based on Standard PN-EN 15241:2011 [5,6].…”
Section: Introductionmentioning
confidence: 99%